An unprecedented up-field shift in the 13C NMR spectrum of the carboxyl carbons of the lantern-type dinuclear complex TBA[Ru2(O2CCH3)4Cl2] (TBA+ = tetra(n-butyl)ammonium cation)1. Issue 30 (14th August 2015) - Hiraoka, Yuya; Ikeue, Takahisa; Sakiyama, Hiroshi; Guégan, Frédéric; Luneau, Dominique; Gillon, Béatrice; Hiromitsu, Ichiro; Yoshioka, Daisuke; Mikuriya, Masahiro; Kataoka, Yusuke; Handa, Makoto
<x xml:space="preserve">Abstract</x> A remarkable up-field shift was found for the carboxyl carbons of TBA[Ru2(O2CCH3)4Cl2] in the 13C NMR spectrum.